Preparation and properties of cellulose nanofibers/α‐zirconium phosphate nanosheets composite polyvinyl alcohol ion‐conductive organohydrogel and its application in strain sensors. Issue 44 (9th September 2022) - Liu, Xinle; Qin, Juhua; Wang, Jing; Chen, Yipeng; Miao, Guohao; Zheng, Junping; Liu, Xiaofei
Abstract: The poor mechanical and electrical properties and single function of conventional conductive hydrogels severely limit their application in flexible sensors. Here, a multifunctional nanomaterial composite high‐strength hydrogel strain sensor was prepared by incorporating α‐zirconium phosphate (α‐ZrP) nanosheets with hydroxyl functional groups on the surface and cellulose nanofibers (CNFs) into a poly(vinyl alcohol) (PVA)matrix simultaneously, using a binary glycerol/water solution as the dispersion medium and a strategy of cyclic freeze–thawing followed by sodium chloride immersion. The experiments showed that CNFs and α‐ZrP nanosheets can form hydrogen bonding interactions with PVA chains, which can synergistically improve the mechanical and electrical properties of the gels with little effect on its transparency, and the tensile strength and elongation at break of the gels can reach 2.42 MPa and 541%, respectively, and the ionic conductivity exceeds 7.65 mS/cm, while possessing a transmission rate of 87% at 600 nm visible light wavelength. In addition, the introduction of glycerol imparts the gel with remodeling, anti‐freezing, and long‐term stability. As a strain sensor, it has a linear sensing range of 0%–350% and high sensitivity (GF = 2.46), and the sensing gloves prepared based on it can accurately and stably recognize letters written by hand. Abstract :